2012
DOI: 10.1002/rcm.6279
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the unknown transformation products derived from clarithromycin and carbamazepine using liquid chromatography/high‐resolution mass spectrometry

Abstract: This study demonstrates that HRMS, combined with LC, is a technique able to play a key role in the evaluation of the environmental fate of pollutants and allows elucidation of the transformation pathways followed by the two drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 33 publications
8
42
0
Order By: Relevance
“…These authors also reported a toxic response in D. magna upon exposure to UV-treated oxycarbazepine solutions. By contrast, Rizzo et al, (2009) observed decreasing toxicity when 5 mg/L carbamazepine solution was treated by TiO 2 photocatalysis, but it should be noted that the degradation pathway under that treatment regime (see Calza et al, 2012) would be different to the uncatalysed photolysis pathway relevant in this experiment.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These authors also reported a toxic response in D. magna upon exposure to UV-treated oxycarbazepine solutions. By contrast, Rizzo et al, (2009) observed decreasing toxicity when 5 mg/L carbamazepine solution was treated by TiO 2 photocatalysis, but it should be noted that the degradation pathway under that treatment regime (see Calza et al, 2012) would be different to the uncatalysed photolysis pathway relevant in this experiment.…”
Section: Discussionmentioning
confidence: 60%
“…However, systematic ecotoxicity testing of treatment transformation products is complicated by the complexity of the relevant degradation pathways and the large numbers of intermediate compounds of varying stability which can be formed (e.g. Agüera et al, 2005;Kosjek et al, 2009;Calza et al, 2012;Li et al, 2012). Moreover, degradation pathways may differ depending on the particular wastewater treatment regime or natural degradation pathway in question (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors suggest that CDOM occurrence would inhibit CBZ direct photolysis by an inner-filter effect, 18,23,24 others underline the key role of CDOM as photosensitiser, although the reactive species involved in CDOM photosensitization were not reported. 17,[19][20][21] Additionally, and perhaps most importantly, despite the many studies aimed at identifying CBZ phototransformation intermediates under a wide variety of environmentally or technologically significant conditions, e.g., [27][28][29][30] there has been no attempt so far to predict or model the formation kinetics of intermediates in the environment, let alone under variable conditions of water chemical composition and depth. Finally, because of the large overlap between CBZ biotransformation and phototransformation metabolites/intermediates, the same compounds are produced by quite different processes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, because of the large overlap between CBZ biotransformation and phototransformation metabolites/intermediates, the same compounds are produced by quite different processes. 1,[27][28][29][30][31] Largely out of this reason, to date there is no indication of which intermediates could be used as reliable markers of CBZ phototransformation in the environment. Therefore, it is presently not possible to distinguish between human metabolism, the (however limited) WWTP processing and photochemistry, as sources of CBZ intermediates in surface waters.…”
Section: Introductionmentioning
confidence: 99%
“…The Orbitrap is, however, gaining popularity for the identification of metabolites due to its sensitivity, large dynamic range and its ability to use an external calibration as opposed to an internal calibration to maintain high accuracy (as in the qTOF) [23,25,26].…”
Section: Introductionmentioning
confidence: 99%